THE INFLUENCE OF PROMOTIONAL COST AGAINTS SALES VOLUME PRODUCT BATIK JAMBI SELARAS PINANG MASAK IN JAMBI CITY - MUHAMMAD IHSAN; ADE PERDANA SIREGAR (Journal of Business Studies and Management Review, 2018)
The purpose of this study are: (1) Identify the influence between the promotional cost against sales volume products batik local craft. (2) Identify the variable costs of the dominant promotion affects the sales volumes of local handicraft products batik. Analytical tools used in this research is to test assumptions, multiple regression analysis, T test and F test. The location of the research on Selaras Pinang Masak on JL. KH. Jakfar RT. 01 Mudung Laut, Peelayangan in Jambi City. Based on the test results proved that partially variable cost of sales promotions and personnel costs selling that can provide significant effects against the volume of sales of products batik on Selaras Pinang Masak in Jambi City, while variable costs of advertising and the cost of publicity does not influence significantly to sales volumes of products batik on Selaras Pinang Masak in Jambi City. Based on the results of the calculations found that the variable cost of sales promotions and personnel costs selling that has significant influence against the volume of sales of products batik on Saanggar Selaras Pinang Masak in Jambi City, in the study the independent variables that influence the dependent variable was dominant against the cost of sales promotions